Output-power equivalence of two- and four-terminal photovoltaic-thermoelectric hybrid tandems. (1st January 2023) - Sakuma, Jun; Kamide, Kenji; Mochizuki, Toshimitsu; Takato, Hidetaka; Akiyama, Hidefumi
Abstract : Two- and four-terminal photovoltaic (PV)–thermoelectric (TE) hybrid tandems are studied theoretically based on the scaling of coupled nonlinear equations for heat and electrical currents. We generally prove the equivalence between achievable output powers by two- and four-terminal tandems. If the PV and TE segments are adjusted in terms of numbers, areas, and connections in a four-terminal tandem, lossless matching is always possible in current or voltage for series or parallel two-terminal tandems while maintaining other designs, materials, or installation environments. That is, the same output power is always achievable in two- and four-terminal tandems using such adjustments.